2016
DOI: 10.1371/journal.pone.0153328
|View full text |Cite
|
Sign up to set email alerts
|

Does Whole-Body Hypothermia in Neonates with Hypoxic–Ischemic Encephalopathy Affect Surfactant Disaturated-Phosphatidylcholine Kinetics?

Abstract: BackgroundIt is unknown whether Whole-Body Hypothermia (WBH) affects pulmonary function. In vitro studies, at relatively low temperatures, suggest that hypothermia may induce significant changes to the surfactant composition. The effect of WBH on surfactant kinetics in newborn infants is unknown. We studied in vivo kinetics of disaturated-phosphatidylcholine (DSPC) in asphyxiated newborns during WBH and in normothermic controls (NTC) with no or mild asphyxia. Both groups presented no clinically apparent lung d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…HIE is a neonatal brain injury disease characterized by changes in muscle tone or hypotension, convulsions and other clinical symptoms, and serious illness can lead to death in children (11). As one of the most effective methods for the treatment of HIE, sub-hypothermia treatment reduces the temperature of the body by 2–5°C, thereby reducing the level of adenosine triphosphate (ATP) in the brain cells and reducing lactic acid accumulation, which in turn reduces the levels of excitatory neurotransmitters, inflammatory mediators and other cytotoxins, so as to protect the nerves (12).…”
Section: Discussionmentioning
confidence: 99%
“…HIE is a neonatal brain injury disease characterized by changes in muscle tone or hypotension, convulsions and other clinical symptoms, and serious illness can lead to death in children (11). As one of the most effective methods for the treatment of HIE, sub-hypothermia treatment reduces the temperature of the body by 2–5°C, thereby reducing the level of adenosine triphosphate (ATP) in the brain cells and reducing lactic acid accumulation, which in turn reduces the levels of excitatory neurotransmitters, inflammatory mediators and other cytotoxins, so as to protect the nerves (12).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the MAS involves inflammatory response characterized by a predominantly neutrophilic infiltrate and stimulation of inflammatory cytokines (e.g., interleukin [IL]-1, IL-6, IL-8 and tumor necrosis factor [TNF]-α) [3][4][5] . The aim of MAS treatment focuses on minimizing ongoing injury, maintaining oxygenation, and reducing inflammation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another possible explanation for the improvement in surfactant activity, is that hypothermia could stimulate the in vivo production or secretion of endogenous surfactant. However, DPPC pool and half-life have been reported to be unaffected by WBH [ 11 ]. Variations in other surfactant phospholipids or, alternatively, mobilization of surfactant components from pre-existing reservoirs could also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…However, D9-choline labeling of healthy volunteers showed that upper airways samples still reflect alveolar PC composition and metabolism [ 41 ]. The fibroscopic technique is not suitable in neonates due to the small patients’ size and studies on neonatal lung biology are commonly done with the non-bronchoscopic BAL [ 9 , 11 , 25 , 28 ]. Moreover, our technique for non-bronchoscopic BAL is standardized and is known to describe the alveolar milieu better than the simple tracheal aspirates [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation